Defining success in education: Exploring the frames of reference used by different voluntary migrant groups in Belgium. (November 2015) - Van Praag, Lore; Stevens, Peter A.J.; Van Houtte, Mieke
Highlights: Ogbu's theory is explored by examining three voluntary immigrant groups. Immigrant students use distinct frames of reference and daily comparison groups. The use of particular comparison groups depends on immigrant group characteristics. Students' comparison groups are used to make educational choices (e.g. tracks). Abstract: There has been little research, particularly in Europe, into who ethnic minority students compare themselves to in developing attitudes towards education and in making educational decisions, and into how their use of particular frames of reference can be explained. The analyses are derived from qualitative interviews and ethnographic observations involving students from Eastern European ( N  = 15), Turkish ( N  = 33), and Northern African descent ( N  = 18) from three secondary schools in Flanders (Belgium) providing academic, technical, and vocational tracks. This study finds that the generational status of immigrants, their experienced collective problems, the structural characteristics of the immigrant networks, and related access to resources shape students' use of particular reference groups. This, in turn, seems to explain particular educational outcomes. The conclusion discusses the implications of this study for future research and social policy.